4-Connected azabicyclo[5.3.0]decane Smac mimetics-Zn2+ chelators as dual action antitumoral agents. Issue 11 (1st June 2017) - Manzoni, Leonardo; Samela, Alessandro; Barbini, Stefano; Cairati, Silvia; Penconi, Marta; Arosio, Daniela; Lecis, Daniele; Seneci, Pierfausto
Graphical abstract: Abstract: Putative dual action compounds (DACs3a –d ) based on azabicyclo[5.3.0]decane (ABD) Smac mimetic scaffolds linked to Zn 2+ -chelating 2, 2′-dipicolylamine (DPA) through their 4 position are reported and characterized. Their synthesis, their target affinity (cIAP1 BIR3, Zn 2+ ) in cell-free assays, their pro-apoptotic effects, and their cytotoxicity in tumor cells with varying sensitivity to Smac mimetics are described. A limited influence of Zn 2+ chelation on in vitro activity of DPA-substituted DACs3a –d was sometimes perceivable, but did not lead to strong cellular synergistic effects. In particular, the linker connecting DPA with the ABD scaffold seems to influence cellular Zn 2+ -chelation, with longer lipophilic linkers/DAC3c being the optimal choice.